Effect of wheat hay particle size and replacement of wheat hay with wheat silage on rumen pH, rumination and digestibility in ruminally cannulated non-lactating cows. (9th September 2016) - Shaani, Y.; Nikbachat, M.; Yosef, E.; Ben-Meir, Y.; Friedman, N.; Miron, J.; Mizrahi, I.
Abstract : This study examined the effects on intake, diurnal rumen pH changes, rumination and digestibility of feeding ruminally cannulated non-lactating cows in a Latin square design (four cows×four periods) with four total mixed rations (TMRs) typical for lactating cows. TMRs were based on: long wheat hay or short wheat hay, wheat silage or wheat silage+1.5% NaHCO3 buffer, as the sole roughage source (30% of TMR dry matter (DM)). The level of physically effective NDF remaining above the 8 mm screen (peNDF) was similar in the long hay and silage-based TMRs (9.45% to 9.64% of DM) and lower in the short hay TMR (7.47% of DM). The four TMRs were offered individually at 95% of ad libitum intake to avoid orts within 24 h. Cows fed long hay consumed less DM than the short hay and silage groups (9.6 v. 10.5 and 10.8 kg/day, respectively) and sorted against large hay particles at 12 h post-feeding. Under the limitations of this study (non-lactating cows fed at restricted intake) short hay TMR prevented sorting within 12 h post-feeding, encouraged rumination per kg peNDF ingested, and had higher average rumen pH (6.24), whereas preventing sub acute ruminal acidosis (SARA, defined as pH<5.8 for at least 5 h/day). In contrast, the long hay and silage-based groups were under SARA. In vitro methane production of rumen fluid was higher in the hay-fed cows than in their silage-fed counterparts, and in all treatments lower at 1 h pre-feeding than at 6 h post-feeding. In vivo DM and NDF digestibility were similar for the short hay and silage TMRs, and higher than those of the long hay TMR. Under the conditions of this study, addition of 1.5% buffer to the wheat silage TMR had no effect on intake, rumen pH, creation of SARA and digestibility.